PENGARUH TiO2 DAN pH PADA FOTOREDUKSI ION Cu(II) DALAM LARUTAN YANG MENGANDUNG PARACETAMOL - Ingrid A, Devina; Angeliasari , S. (Jurnal Farmasi (Journal of Pharmacy), 2016)
Research on photoreduction of Hg(II) solution containing p-chlorophenol has been done. In photocatalitic approach, this study tried to overcome environmental problem due to Hg-polluted water that is still a seriuous problem now. Photocatalist material, such as TiO2 have been developed to support the effort in solving such a problem. One of negative impact of industrial development is disposal of waste water generated from industrial activities. Industrial waste water may contain inorganic and organic chemicals. Anorganic waste such as Cu(II) in the aquatic environment has a threshold of 1 mg/L that present together with organic waste such as paracetamol. This study is purposed to determine the effect of TiO2 mass and pH, and optimum conditions of TiO2 catalyzed Cu(II) photoreduction effectiveness. Photocatalysis combines ultraviolet irradiation and semiconductor particles as photocatalysts in chemical proccess. Cu(II) photoreduction process was conducted in a closed reactor equipped with a magnetic stirre and UV lamp black light blue (BLB). After process solution was then analyzed by Atomic Absorption Spectrophotometer (AAS) to determine the remaining Cu(II) concentration and visible spectrophotometer to determine the remaining paracetamol. Results show that Cu(II ion was reduced increasingly withy mass of TiO2. Within TiO2 range of 20 to 25 mg Cu(II) reduction increase moderately, TiO2 mass of 30 to 50 mg was reduction was decreased. Variation of solution pH, within pH 3 to 5 shows the reduction occure effectively, while it would decrease at pH 5 to 11. Reaction conditions that produce the the most effective process are pH 5, Cu(II) concentration of 10 mg/L 25 mL, with the addition of 25 mL paracetamol 300 mg/L, TiO2 of 25 mg, with irradiation time of 30 minutes. In these conditions Cu(II) ion was reduce effectively by 98.70% and paracetamol degraded by 14.61%.